(untitled) (Circe de clásicos y modernos, 2018)
Philo gives Israel an etymology which is original in the biblical hermeneutics but will be repeated by the later Patrology. Israel is “he who sees God”, “the race/ class, which is capable of seeing” or simply “the one that can see”. The praise of the sight brings Platonic reminiscences to the Philonic texts, but our research especially follows the history of the term in the tradition of the Scriptures which consider Israel the chosen people submitted to established and defined rules by the revelation of God Himself. We’ll see the range of the quality of being Jew or proselyte in the works of Philo and the way in which the term Israel generously expands its limits to include in the concept not only who belong to a nation (éthnos) but to a class (génos) that constitutes a philosophical category.